Harmonization of the Concept of Maqashid Shariah and SDGs: A Review - Fitria, Lia (Management and Sustainability, 2023)
This research aims to assess the progress of studies on "Maqasid Shariah SDGs" from 2018 to 2023 and identify research plans based on articles related to this topic. Qualitative methods with a bibliometric analysis approach were used in this research. Secondary data focused on the theme "Maqasid Shariah SDGs" was obtained from the Dimensions database, covering a total of 38 articles. Next, the data was processed and analyzed using the VosViewer application to form a bibliometric map regarding the development of "Maqasid Shariah SDGs" research in general. The research results show that there are 3 main clusters in the topic "Maqasid Shariah SDGs" based on keyword mapping analysis, which can be used as research direction, namely "Islamic finance, Maqasid shariah, and SDGs", "Waqf, Maqasid shariah, and SDGs", and "Problems and challenges in maqasid sharia and SDGs". For the future, it is necessary to develop a research agenda related to "Maqasid Shariah SDGs", for example in the context of the non-financial halal industrial sector such as halal tourism, halal food, halal pharmacies, and so on. This is interesting to research because it has not been covered in the lines of research that have been carried out.